The Quality Assurance System of HKU SPACE: The Implementation of Collaborative Quality Assurance for Programs in Library and Information Studies with Charles Sturt University. Issue 4 (2nd October 2018) - Ma, Leo F. H.; Yu, Ling Ling
ABSTRACT: Quality assurance (QA) management has been used by educational institutions as a tool to control and measure the academic output and achievement of the faculty. The School of Professional and Continuing Education of the University of Hong Kong (HKU SPACE) implemented a QA System in 1999 for its programs including the collaborative programs offered by the HKU SPACE and its academic partners. This paper examines the structure and implementation of the QA System, introduces the conceptual framework of the QA System and discusses in detail the Quality Review Process (QRP) and QA exercise of the collaborative library and information studies (LIS) programs offered by the HKU SPACE and the Charles Sturt University (CSU). The QA System can be used to reflect on and appraise objectively the quality and effectiveness of collaborative LIS programs jointly offered by the HKU SPACE and CSU, and also similar quality review programs can be used in other contexts. It should however be noted that caution should be taken to prevent the QRP from becoming just a superficial exercise. This paper can be used as a case study in the discussion of adopting QA management in educational institutions and contexts.